Cultural algorithms : tools to model complex dynamic social systems - Reynolds, Robert G. (Piscataway, NJ : IEEE Press ; Hoboken, New Jersey : John Wiley & Sons, Inc., 2021)
""The Foundations of Social Intelligence" covers a wide range of the basic framework of cultural algorithms, from the history of its development to how other nature-inspired algorithms can be expressed. It also demonstrates how the social organizational structures that make up human socio-political systems can be modeled in terms of cultural algorithms. It explores how the learning process is expressed in thermodynamic terms as a cultural engine, while proposing several social metrics to assess their performance. Cultural algorithms are a computational framework for understanding human social evolution based upon anthropological and archaeological models of cultural evolution. The key is how we can we use cultural algorithms as a vehicle to understand why these building blocks are ubiquitous across the globe in computational terms. The performance of the basic social models are compared against each other relative to the different categories of complex systems problems"--
Fitness Function -- Dataset and Observation -- Summary and Conclusion -- 7. Evolving Emergent Team Strategies in Robotic Soccer using Enhanced Cultural Algorithms -- Abstract -- Introduction -- Related Work -- The 2D Soccer Simulation Testbed -- Evolution of team strategies via Cultural Algorithm -- Experiments and Analysis of Results -- Conclusion -- References -- 8. The Use of Cultural Algorithms to Learn the Impact of Climate on Local Fishing Behavior in Cerro Azul, Peru -- Introduction -- An Overview of the Cerro Azul Fishing Data Set -- Data Mining at the Macro, Meso, and Micro Levels -- Cultural Algorithms and Multi-Objective Optimization -- The Artisanal Fishing Model -- The Experimental Results -- Statistical Validation -- Conclusions and Future Work -- 9. CAPSO: A Parallelized Multiobjective Cultural Algorithm Particle Swarm Optimizer -- Introduction -- Multi-Objective Optimization -- Cultural Algorithms -- CAPSO Knowledge Structures -- Tracking Knowledge Source Progress (Other than Topographic) -- CAPSO Algorithm Pseudocode -- Multiple Runs -- Benchmark Problems Comparison -- Overall Summary of Results -- Other Applications -- 10. Exploring Virtual Worlds with Cultural Algorithms: Ancient Alpena-Amberley Land Bridge -- Archaeological Challenges -- Generalized Framework -- The Land Bridge Hypothesis -- Origin and Form -- Putting Data to Work -- Path-Finding and Planning -- Identifying Good Locations -- Cultural Algorithms -- Cultural Algorithm Mechanisms -- The Composition of the Belief Space -- Future Work -- Path Planning Strategy -- Local Tactics -- Detailed Locational Information -- Extending the Cultural Algorithms -- Human Presence in the Virtual World -- Increasing the Complexity -- Updated Path-Planning Results -- The Fully Rendered Land Bridge -- Pathfinder Mechanisms -- Results -- Conclusions.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on February 24, 2021).
John Wiley and Sons
Keywords: Social systems -- Mathematical models; Culture -- Mathematical models; Algorithms; Social intelligence; Computational intelligence; Algorithms; Emotional Intelligence; x; Algorithmes; Intelligence sociale; Intelligence informatique; algorithms; Algorithms; Computational intelligence; Culture -- Mathematical models; Social intelligence; Social systems -- Mathematical models